PLANNING AND MONITORING OPERATIONAL COSTS FOR PURCHASING GOODS - Ritonga, Wardoni Hikman; Nasution, Yenni Samri Juliati; Anggraini, Tuti (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
Planning and monitoring operational costs, including the costs of purchasing goods, are crucial for companies to achieve the goal of maximizing profit by minimizing costs. This study aims to understand and develop operational cost management practices, particularly in the context of goods purchasing, and to assess the effectiveness of planning and monitoring at PT UNEFECO. The research employs a descriptive method with a qualitative approach, utilizing observation, interviews, and document analysis. The results indicate that the planning and monitoring of operational costs for purchasing goods at PT UNEFECO have not reached the desired level of effectiveness. There are significant discrepancies between the planned and actual costs, despite the identification of some favorable variances. This suggests inaccuracies in cost estimation, a lack of effective control, or unexpected changes in market conditions. These findings highlight the need for improvements in planning and monitoring operational costs for purchasing goods at PT UNEFECO to reduce the gap between planned and actual budgets, enhance cost estimation accuracy, and improve operational control effectiveness.